Autonomous cyber deception : reasoning, adaptive planning, and evaluation of HoneyThings /: reasoning, adaptive planning, and evaluation of HoneyThings. (2019) - Al-Shaer, Ehab S, 1967-; Wei, Jinpeng; Hamlen, Kevin; Wang, Cliff
No abstract available